The Surviving Sepsis Campaign: Fluid Resuscitation and Vasopressor Therapy Research Priorities in Adult Patients. Issue 4 (April 2021) - Lat, Ishaq; Coopersmith, Craig M.; De Backer, Daniel; Coopersmith, Craig M.; De Backer, Daniel; Deutschman, Clifford S.; Evans, Laura; Ferrer-Roca, Ricard; Hellman, Judith; Jog, Sameer; Kesecioglu, Jozef; Lat, Ishaq; et al.
Abstract : OBJECTIVE: Expand upon the priorities of fluid resuscitation and vasopressor therapy research priorities identified by a group of experts assigned by the Society of Critical Care Medicine and the European Society of Intensive Care Medicine. DATA SOURCES: Original article, literature search. STUDY SELECTION: Several members of the original task force with expertise specific to the area of fluid resuscitation and vasopressor therapy. DATA EXTRACTION: None. DATA SYNTHESIS: None. CONCLUSION: In the second of a series of manuscripts subsequent to the original article, members with expertise in the subjects expound upon the three identified priorities related to fluid resuscitation and vasopressor therapies. This analysis summarizes what is known and what were identified as ongoing and future research.